The association of muscle weakness with functional disability in older patients with Diabetes mellitus: Measured by three different grip strength thresholds - Sibel Çavdar; Fatma Ozge Kayhan Koçak; Sumru Savas (PLoS ONE, 2025)
The association of muscle weakness with poor outcomes is well defined in general older population, but there is insufficient data on the association of muscle weakness with functionality in older patients with diabetes mellitus (DM). We aimed to investigate the predictivity of muscle weakness defined as low grip strength thresholds determined by EWGSOP2, and two regional thresholds in older patients with DM for functional disability. Activities of Daily Living (ADL), Instrumental ADL (IADL), grip strength, comorbidities, anthropometric and biochemical data from outpatient clinic medical records were screened retrospectively. Low grip strength was determined by EWGSOP2, and two regional thresholds. Receiver operating characteristic (ROC) analysis, sensitivity and negative predictive values were conducted to identify the discrimination power of three different grip strength thresholds for functional disability in patients with DM. A total of 197 patients with DM and 215 controls were included. In ROC analyses, regional thresholds were with higher sensitivity and negative predictive values for functional disability in both groups. For patients with DM, regional normative thresholds predicted functional disability both for ADLs and IADLs whereas for patients without DM normative thresholds predicted ADL, and calculated thresholds predicted IADL disability. Regional normative thresholds predicted both ADL and IADL functional disability in older patients with DM.